Procedures for Fecal Microbiota Transplantation in Murine Microbiome Studies - Bokoliya, Suresh C.; Dorsett, Yair; Panier, Hunter; Zhou, Yanjiao (Frontiers in Cellular and Infection Microbiology, 2021)
Fecal microbiota transplantation (FMT) has been widely recognized as an approach to determine the microbiome’s causal role in gut dysbiosis-related disease models and as a novel disease-modifying therapy. Despite potential FMT results in various disease models, there is a variation and complexity in procedural agreement among research groups for performing FMT. The viability of the microbiome in feces and its successful transfer depends on various aspects of donors, recipients, and lab settings. This review focuses on the technical practices of FMT in animal studies. We first documented crucial factors required for collecting, handling, and processing donor fecal microbiota for FMT. Then, we detailed the description of gut microbiota depletion methods, FMT dosages, and routes of FMT administrations in recipients. In the end, we described assessments of success rates of FMT with sustainability. Overall, this review highlights various methods that may lead to developing the standard and reproducible protocol for FMT.